2007
DOI: 10.1061/(asce)0733-950x(2007)133:6(414)
|View full text |Cite
|
Sign up to set email alerts
|

Source Constraints and Model Simulation of the December 26, 2004, Indian Ocean Tsunami

Abstract: The December 26, 2004 tsunami was perhaps the most devastating tsunami in recorded history, causing over 200,000 fatalities and widespread destruction in countries bordering the Indian Ocean. It was generated by the third largest earthquake on record ͑M w = 9.1-9.3͒ and was a truly global event, with significant wave action felt around the world. Many measurements of this event were made with seismometers, tide gauges, global positioning system stations, and a few satellite overpasses. There were numerous eyew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(86 citation statements)
references
References 38 publications
1
84
1
Order By: Relevance
“…However, time lags of 6-10 min are observed at other station. Similar time lags were shown in the comparison of FUNWAVE's result and measurement in Grilli et al (2007).…”
Section: Verification Of the Tunami-n2-nus Modelsupporting
confidence: 64%
See 2 more Smart Citations
“…However, time lags of 6-10 min are observed at other station. Similar time lags were shown in the comparison of FUNWAVE's result and measurement in Grilli et al (2007).…”
Section: Verification Of the Tunami-n2-nus Modelsupporting
confidence: 64%
“…An interesting conclusion from his study is that numerical dispersion in coarser grid made the solution better than higher-order model with the same grid length and even the same model at finer grid. Recently, Grilli et al (2007) compared numerical results of NSWE and Boussinesq simulations for the Indian Ocean (2004) Tsunami. Their study showed a remarkable difference of surface elevation (∼20%) west of the source, in deep water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of the physical processes of the seismic source, describing the bottom motion becomes rather challenging [Banerjee et al, 2005;Ammon et al, 2005;Pietrzak et al, 2007;Grilli et al, 2008], and simulating the dynamical processes in the tsunami and AGWs source becomes complicated [Nosov and Kolesov, 2007]. Notwithstanding, it is known that properties of AGWs depend on rupture model parameters such as the vertical and lateral extent and duration of bottom motion [Yamamoto, 1982;Nosov, 1999;Chierici et al, 2010;Stiassnie, 2010;Hendin and Stiassnie, 2013].…”
Section: Key Pointsmentioning
confidence: 99%
“…The variation (uncertainty) in the output of a numerical model can be apportioned, qualitatively or quantitatively, through a sensitivity analysis, to different sources of variation in the input of the model. The publications about this type of analysis are numerous (e.g., Weisz and Winter, 2005;Grilli et al, 2007;Dao and Tkalich, 2007;Synolakis et al, 2007;Hébert et al, 2007).…”
Section: Introductionmentioning
confidence: 99%